Operational Procedures Describing Physical Systems - Agop, Marciel; Merches, Ioan; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The authors examine topics in modern physics and offer a unitary and original treatment of the fundamental problems of the dynamics of physical systems, as well as a description of the nuclear matter within a framework of general relativity. They show that some physical phenomena studied at two different resolution scales (e.g. microscale, cosmological scale), apparently with no connection between them, become compatible by means of the operational procedures, acting either as some (3y(Bhidden(3y (Bsymmetries, or harmonic-type mappings. The book is addressed to the students, researchers and university/high school teachers working in the fields of mathematics, physics, and chemistry.s
1 From Kepler problem to skyrmions -- 2 Spherical metrics in general relativity -- 3 The gravitational and stationary electro-magnetic fields -- 4 Frames, measurements and field variables -- 5 Role of surface gauging in extended particle interactions: the case for spin -- 6 The classical theory of light colors: a paradigm for description of particle interactions.
Includes bibliographical references and index.
Also available in print format.
Keywords: Physics; Dynamics; Relativity; Mathematical physics; SCIENCE / Mathematical Physics; SCIENCE / Physics; asymptotic freedom; fractal-type theories; hidden symmetries; Kepler motion dynamics; relativity; skyrmionic models; Electronic books